Analysis of the SER/ESTAR opposition based on the origins and evolution of {st} saliencing : a submorphological and enactive approach. (Signifiances (Signifying), 2017)
The theory of submorphemic saliencing has tried to show that the notion of « stability » is often expressed in Spanish through words that include the consonantal group {st}. However, this saliencing is the constitutive marker of the verb estar’s paradigm, generally associated with accidental or circumstantial existence with no essentialising projection, as opposed to the verb ser. Taking a diachronic and synchronic approach based on the signifier, this article aims to explain and understand this apparent contradiction, i.e. the systemic and semantic opposition between ser and estar (sedere/stare). The hypothesis defended in this study is that we are faced with a semantic opposition that can also be seen at the level of the signifiers, which are opposed in two different configurations offering an illustrative example of the motivation of the sign.